Response of rapeseed growth to soil salinity content and its improvement effect on coastal saline soil - Wang, Haoming; Li, Yiyang; Huang, Yihang; Wang, Yan; Qu, Wenting; Lin, Yaowei; Wang, Long; Lin, Guobing; Zuo, Qingsong (Frontiers in Plant Science, 2025)
Coastal saline soil is considered an important land source due to their abundant thermal and light conditions, irrigation resources, and relatively low reclamation difficulty. However, it is crucial to establish effective strategies for ameliorating saline soil to render it suitable for crop growth and development. As an economic crop with strong salt tolerance, rapeseed (Brassica napus L.) may be a pioneer crop for the development and utilization of saline-alkali lands. To explore the adaptability of rapeseed in coastal saline soils and its potential for soil improvement, this study conducted rapeseed cultivation experiments in soils with different salinity levels over three consecutive years. Prior to sowing in the first season, the initial soil salinity levels were measured at 2.49 g kg−1 (low-salinity soil, LS) and 4.27 g kg−1 (high-salinity soil, HS). The seed yield and biomass of rapeseed, soil physiochemical properties, and soil enzyme activity were investigated. The results revealed that the seed yield and biomass of rapeseed in high-salinity soil were significantly reduced by 40.30% and 30.58% across three growing seasons, compared to low-salinity soil. As the cultivation year progressed, the seed yield and biomass gradually increased. After three years of rapeseed cultivation, total salt content reduced from 2.50–4.20 g kg−1 to 1.59–2.79 g kg−1, and EC decreased from 0.95–1.38 ms cm−1 to 0.32–0.40 ms cm−1. Compared to bare land, rapeseed cultivation exhibited a reduction in soil bulk density, along with an increase in porosity and proportions of macro- and micro-aggregates. In terms of chemical properties, after rapeseed cultivation, the contents of organic matter, dissolved organic C, total N, available N, total phosphorus, available phosphorus increased by 56.99%, 10.49%, 47.13%, 64.43%, 19.30%, and 74.31% in the low-salinity soil; correspondingly, the increases in the high-salinity soil were 22.83%, 3.57%, 8.81%, 22.96%, 11.81%, and 53.82%. In addition, rapeseed cultivation augmented the activity of β-glucosidase, urease, protease, and alkaline phosphatase in both low-salinity and high-salinity soils. Overall, rapeseed proved to be an appropriate crop for the remediation of coastal saline soil, effectively ameliorating soil quality by reducing salinity, fortifying soil structure, accumulating nutrients, and fostering soil enzyme activity.